Perlindungan Hukum terhadap Tenaga Kerja Penyandang Disabilitas Fisik dalam Perspektif Hukum Ketenagakerjaan dan UU No.8 Tahun 2016 tentang Penyandang Disabilitas - Purwinarto, Dona Putri; Faizah, Syarifah; Amanda, Cindy Pricillia; Aminah, Siti; Hafsah, Riana Yuni; Rumapea, Erika Hotmauly; Septiani, Sofi Aldini; Ramadanti, Cantika; Wijaya, Mustika Mega (AHKAM, 2023)
People with disabilities also have the same rights as citizens. In fact, there is still a lot of discrimination of the rights of persons with disabilities in working and looking for work. The usefulness of this research is as a reference for development efforts in the field of law, especially in the field of labor regarding the application of legal protection for persons with disabilities. The purpose of this research is to provide knowledge to readers in understanding the importance of the role of society, government, and companies in respecting the rights of persons with disabilities. This research uses juridical-normative research methods by reviewing the law from various aspects and approaches to the legislation concerned. The nature of this research is descriptive-analytical research, which is a method of taking existing data so that it can be described more fully. Persons with disabilities have the right to obtain guarantees of legal protection through guarantees of rights that are expressly stated in laws and regulations regarding persons with disabilities, including having guarantees of freedom from neglect, exclusion, discrimination, threats to respect for integrity. Persons with disabilities have the right to get a job according to the level of disability as well as employers guarantee the protection of workers with disabilities according to the level of disability of these workers.